New Thermosetting Resin from Benzoxazine and Cyanate Ester Resin. Issue 1 (31st August 2012) - Kimura, Hajime; Ohtsuka, Keiko; Matsumoto, Akihiro
Abstract A curing reaction of benzoxazine with cyanate ester resin and the properties of the cured new thermosetting resin were investigated. In particular, the effect of the content of cyanate ester resin on the cure behavior and the properties of the cured new thermosetting resins were investigated. As a result, it was found that the ring‐opening reaction of a benzoxazine ring and thermal self‐cyclotrimerization of a cyanate ester group occurred, then the phenolic hydroxyl group generated by the ring‐opening reaction of the benzoxazine ring might coreact with the cyanate ester group. As the content of cyanate ester resin increased, the gelation reaction proceeded more quickly. The cured new thermosetting resin from benzoxazine and cyanate ester resin showed good thermal stability, high electrical resistivity, and high water resistance. As the content of cyanate ester resin increased, the glass transition temperature and electrical resistivity became especially higher. © 2012 Wiley Periodicals, Inc. Adv Polym Techn 32: E651–E659, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/adv.21308